Chemical and isotopic evidences on evaporite dissolution as the origin of high sulfate water in a karst geothermal reservoir. (October 2022) - Bao, Yifan; Pang, Zhonghe; Huang, Tianming; Li, Yiman; Tian, Jiao; Luo, Ji; Qian, Tingqing
Abstract: Using multiple isotopes including 87 Sr/ 86 Sr in water, δ 34 SSO4, δ 18 OSO4, δ 18 OH2O and δ 2 HH2O, δ 13 CDIC and 14 CDIC in water, we have investigated the origin and evolution of sulfate concentration (1472 mg/L) in the Tangquan Karst geothermal system in Nanjing, China. The sulfate has been found to be mainly derived from dissolution of gypsum and other evaporite minerals occurring in the carbonate reservoir. The dissolution of evaporite minerals is relatively easier than carbonate at elevated temperatures. We confirmed this differentiated dissolution process by reverse hydrogeochemical simulation using the PHREEQC code. The origin of sulfate is supported by 87 Sr/ 86 Sr isotope ratio (0.7088–0.709) with a typical marine signature. We further constrained the origin of sulfate with δ 34 S in aqueous SO4 (27.6‰–34.2‰) and δ 18 O in aqueous SO4 (14.3‰–18.4‰). Such sulfate-rich geothermal water usually occurs in open karst geothermal systems, favorable for Spa therapy in many places of the world. Highlights: The source of sulfate in sulfate-rich water is identified to be evaporite dissolution, using the sulfur and oxygen isotope in sulfate and strontium isotope ratio as constraints. The chemical thermodynamic simulation results by SOLVEQ show that the reason for the different hydrochemical types of cold water and geothermal water is due to the solubility difference between carbonate and gypsum minerals at different temperatures.